THE EFFECT OF NON-CASH PAYMENT TRANSACTIONS ON THE VELOCITY OF MONEY IN INDONESIA - Indah Nur Aeni; Harya Kuncara Wiralaga; Dicky Iranto (Transpublika Publisher, 2023)
This study aims to examine the effect of non-cash payment transactions on velocity of money in Indonesia. Specifically, it investigates the impact of electronic money transactions, debit card transactions, credit card transactions, and the COVID-19 pandemic on velocity of money. The research adopts a quantitative approach and utilizes time series data from 2018 to 2021 obtained from the Bank Indonesia website. Multiple linear regression analysis is employed as the analytical technique. The findings reveal that electronic money transactions do not significantly affect velocity of money in Indonesia. Debit card transactions show a negative and significant impact, while credit card transactions do not show a significant effect. Furthermore, the COVID-19 pandemic has a negative and significant influence on the velocity of money in Indonesia. Simultaneously, all the independent variables have a significant effect on the velocity of money in Indonesia. The R2 testing indicates that the independent variables explain 85.94% of the variability in the velocity of money variable, while the remaining 14.06% is attributed to other factors beyond this study.